Strukturni in vsebinski vidiki opomb o rabi v didaktičnem dvojezičnem slovarju za dekodiranje - Vrbinc, Marjeta (Slavistična revija, 2016)
The paper analyzes usage notes included in an English-Slovene dictionary with a strong didactic component. The dictionary contains 333 usage notes, which represent the material for this analysis. The analysis focuses on the language and structure of usage notes. In the main section of the paper, the usage notes are analyzed with regard to the part of speech and to the content of each lemma. The results show that nominal lemmata are most frequently accompanied by usage notes, followed by verbal lemmata and other parts of speech. The majority of usage notes deal with contrastive problems, while some usage notes discuss the characteristics of the source language (i.e., English). The findings of the paper are not limited to one particular language pair, but can be used universally, regardless of the languages in question.
Keywords: angleščina; bilingual dictionaries; contrastive differencies; dictionary users; dvojezični slovarji; English; English language; leksikografija; lexicography; potrebe uporabnikov; Slovene; Slovenian language; slovenščina; uporabniki slovarja; user's needs